Peran Efikasi Diri dalam Memediasi Kesiapan Menjadi Guru - Arifah, Cyntia; Subowo, Subowo; Santoso, Jarot Tri Bowo (Universitas Negeri Semarang, 2021)
The objectives of this research are to know the direct and indirect influence of teachers' professional perception, teacher professional education and family environment on the readiness to become teachers through self efficacy. Data analysis method used is descriptive analysis and regression analysis. The result of descriptive analysis is known that the level of readiness to be a teacher to the students in the high category, the perception of the students about the teacher profession in the good category, the perception of the students about teacher education program (PPG) in good category, student family environment in good category, owned by students in high category. While the perception of teacher profession, family environment, and self efficacy directly affect the readiness to be a teacher to the student while the perception of teacher education (PPG) directly does not affect the readiness to become a teacher to the students. In addition, it can be concluded also that indirect perceptions of the profession of teachers, perceptions of teacher education (PPG), and family environment affect the readiness to become teachers to students through self efficacy.